Parentage Atlas of Italian Grapevine Varieties as Inferred From SNP Genotyping - D’Onofrio, Claudio; Tumino, Giorgio; Gardiman, Massimo; Crespan, Manna; Bignami, Cristina; de Palma, Laura; Barbagallo, Maria Gabriella; Muganu, Massimo; Morcia, Caterina; Novello, Vittorino; Schneider, Anna; Terzi, Valeria (Frontiers in Plant Science, 2021)
The Italian grape germplasm is characterized by a high level of richness in terms of varieties number, with nearly 600 wine grape varieties listed in the Italian National Register of Grapevine Varieties and with a plethora of autochthonous grapes. In the present study an extended SNP genotyping has been carried out on Italian germplasm of cultivated Vitis vinifera subsp. sativa and Vitis hybrids. Several hundred Italian varieties maintained in the repositories of scientific Institutions and about one thousand additional varieties derived from previous studies on European, Southern Italy, Magna Graecia and Georgian germplasm were considered. The large genotyping data obtained were used to check the presence of homonyms and synonyms, determine parental relationships, and identify the main ancestors of traditional Italian cultivars and closely-related accessions. The parentage among a set of 1,232 unique varieties has been assessed. A total of 92 new parent-offspring (PO) pairs and 14 new PO trios were identified. The resulted parentage network suggested that the traditional Italian grapevine germplasm originates largely from a few central varieties geographically distributed into several areas of genetic influence: “Strinto porcino” and its offspring “Sangiovese”, “Mantonico bianco” and “Aglianico” mainly as founder varieties of South-Western Italy (IT-SW); Italian Adriatic Coast (IT-AC); and Central Italy with most varieties being offsprings of “Visparola”, “Garganega” and “Bombino bianco”; “Termarina (Sciaccarello)” “Orsolina” and “Uva Tosca” as the main varieties of North-Western Italy (IT-NW) and Central Italy. The pedigree reconstruction by full-sib and second-degree relationships highlighted the key role of some cultivars, and, in particular, the centrality of “Visparola” in the origin of Italian germplasm appeared clear. An hypothetical migration of this variety within the Italian Peninsula from South to North along the eastern side, as well as of “Sangiovese” from South to Central Italy along the Western side might be supposed. Moreover, it was also highlighted that, among the main founders of muscat varieties, “Moscato bianco” and “Zibibbo (Muscat of Alexandria)” have spread over the whole Italy, with a high contribution by the former to germplasm of the North-Western of the peninsula.